An Analysis of Generation Z's Communication Styles in Public Speaking on the Social Media Platform TikTok - Sutinnarto; Lakna Tulas’un; Khairani, Najmi Rizki (Edusight International Journal of Multidisciplinary Studies, 2025)
The development of social media, particularly the TikTok platform, has introduced a new form of public speaking practice among Generation Z. TikTok serves not only as a medium for entertainment but also as a space for expression, opinion sharing, education, and digital public communication. Generation Z, as TikTok's dominant users, has a unique and distinct communication style compared to previous generations. Therefore, this study aims to analyze Generation Z's communication style in public speaking on the TikTok social media platform. This study used a qualitative approach with descriptive methods. Data were collected through observation of TikTok video content, content analysis, and interviews with several content creators from the Generation Z community. Data analysis techniques included data reduction, data presentation, and drawing conclusions. Data validity was tested using triangulation of sources and techniques. The results show that Generation Z's communication style in public speaking on TikTok tends to be relaxed, expressive, visual-oriented, and communicative. The use of simple language, dynamic intonation, strong nonverbal expressions, and the utilization of TikTok features such as music, text, and visual effects are key characteristics in conveying messages. Furthermore, the short video duration encourages Generation Z to convey messages concisely and directly to the point. This study concludes that TikTok serves as an alternative public speaking medium, shaping new communication styles for Generation Z in the digital age